Chloride Transport in Cracked Concrete Subjected to Wetting – Drying Cycles: Numerical Simulations and Measurements on Bridges Exposed to De-Icing Salts - Kušter Marić, Marija; Ožbolt, Joško; Balabanić, Gojko; Zhychkovska, Olesya; Gambarelli, Serena (Frontiers in Built Environment, 2020)
Although many models for service life predictions have been developed, their application to existing bridges is still not at a satisfactory level. The here presented coupled 3D chemo-hygro-thermo mechanical (CHTM) model can realistically simulate both corrosion phases: initiation and propagation. The focus of this research is the transport processes in cracked and un-cracked concrete before reinforcement depassivation. Realistic environmental conditions with the surface water and chloride contents variable in time are simulated based on the meteorological data for a mountain region where case studies bridges are located. Application of the large quantities of de-icing salts in combination with the poorly designed and executed details resulted in a high chloride content in concrete of the superstructure of both bridges: at the reinforcement level chloride content in cracked concrete elements exceeds the threshold value up to 10 times. Numerical results match well with the chloride content measured on the bridges after 11 and 14 years of service. Accounting for the realistic environmental conditions (wetting-drying cycles, application of de-icing salts only in the winter season, etc.) in the numerical simulations results in the continuous transport processes in concrete and higher chloride content in deeper concrete layers as opposed to the finite element models with the constant boundary conditions.